2022
DOI: 10.1021/acsomega.1c06194
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically Increased Binding Constant of Water-Soluble Cyclodextrin Hyperbranched Polymers: Explored with Diffusion Ordered NMR Spectroscopy (DOSY)

Abstract: We report that the polymerization of cyclodextrin (CD) with epichlorohydrin (ECH) dramatically increases the binding constant of CD to vanillin, from 55 to 8.4 × 10 3 M –1 , by approximately 100 times, as determined by diffusion ordered spectroscopy (DOSY)– 1 H NMR. The binding constant increased with an increase of the ECH content of the polymer, although ECH polymers without CDs showed no affinity at all, suggesting that the hydrophobicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In case of host–guest interaction with cyclodextrins, the diffusion of the complexed substrate is mainly driven by the macrocycle, whose diffusion coefficient is basically unaffected by the interaction with the small molecule. With these premises in mind, D b can be approximated to that of the CD and the bound molar fraction can be easily calculated from Equation (2), thus allowing obtaining the association constant from Equation (3) by a single-point measurement [ 37 ]: K = x b /(C − C 0 x b ) (1 − x b ) where C and C 0 are the concentration of the host (cyclodextrin) and the guest (compound B or MCP), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In case of host–guest interaction with cyclodextrins, the diffusion of the complexed substrate is mainly driven by the macrocycle, whose diffusion coefficient is basically unaffected by the interaction with the small molecule. With these premises in mind, D b can be approximated to that of the CD and the bound molar fraction can be easily calculated from Equation (2), thus allowing obtaining the association constant from Equation (3) by a single-point measurement [ 37 ]: K = x b /(C − C 0 x b ) (1 − x b ) where C and C 0 are the concentration of the host (cyclodextrin) and the guest (compound B or MCP), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…39 DOSY has been shown as an excellent quantitative indicator of binding constants between small molecules, 39,40 and between small molecules and synthetic polymers. 41 In 2015 Aroulmoji et al demonstrated that DOSY studies on hyaluronatemethotrexate conjugates with bovine serum albumin produced dissociation constants of an equivalent order of magnitude to that from classical fluorescence titrations, 42 and shortly afterwards Denis-Quanquin et al demonstrated that the diffusion constants between paramagnetic inorganic complexes and proteins could be easily extrapolated to monitor protein binding to trisdipicolinate lanthanide complexes. 43 Although these are some examples where DOSY has been employed to provide binding information, NMR method traditionally used to ascertain this information is primarily via 1 H chemical shift changes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, extensive research on cyclodextrins (CDs) and their complexes with drugs has been carried out using computer simulations [17][18][19][20][21][22][23][24] and experiments [19][20][21][22][25][26][27][28][29][30][31][32][33] In order to develop new DDSs. For example, recent experimental research on the inclusion complex of cyclodextrins and angiotensin-converting enzyme (ACE) showed that the formation of the inclusion complex improves the thermal stability in aqueous solutions which in turn provides for the stabilization of the drug in the aqueous eye drop medium [34].…”
Section: Introductionmentioning
confidence: 99%